COVID-19: Intranasal and Oral Routes of Vaccination - Robinson, Jared; Leclézio, Alexandra; Banerjee, Indrajit (Journal of Lumbini Medical College, 2021)
The mainstay protocol exercised by global health leaders to control the spread of severe acute respiratory syndrome corona virus (SARS-CoV-2) has been screening, the identification of cases, isolation thereof, contact tracing and nation-wide lockdowns. The development of vaccinations against the SARS-CoV-2 virus has marked a new dawn for the war against corona virus disease (COVID-19).